Posterior Capsular Outcomes of Pediatric Cataract Surgery With In-The-Bag Intraocular Lens Implantation - Fu, Yana; Wang, Dandan; Ding, Xixia; Chang, Pingjun; Zhao, Yinying; Hu, Man; Li, Zhangliang; Zhao, Yun-e (Frontiers in Pediatrics, 2022)
AIM: To investigate the change of posterior capsular outcomes of pediatric cataract surgery with primary in-the-bag intraocular lens (IOL) implantation. METHODS: We conducted a case series of pediatric cataract children who underwent cataract extraction with primary in-the-bag IOL implantation, posterior capsulorhexis or vitrectorhexis, and limited anterior vitrectomy at the Eye Hospital of Wenzhou Medical University between 2016 and 2019. Digital retro-illumination photographs of pediatric eyes were obtained at baseline and 6 months, 12 months, and the last visit postoperatively. Capsular outcomes of the posterior capsular opening area (PCOA) and lens reprolifration area at those time points were compared. Correlations between the PCOA and influential factors, such as age at surgery, axial growth, and follow-up duration, were analyzed. The study was registered at register.clinicaltrials.gov (NCT04803097). RESULTS: Data of 23 patients (27 eyes) were used in the final analysis. During follow-up, the PCOA enlarged at a rate of 0.29–0.32 mm2/month during the first six months postoperatively and 0.05–0.08 mm2/month over the next 1–2 years. Six months postoperatively, the PCOA enlargement statistically and positively correlated with the follow-up duration and axial growth. The area of lens reprolifration was 0.46 ± 1.00 mm2 at six months postoperatively and then remained stable. CONCLUSION: The PCOA enlarged rapidly within the first six months after the pediatric cataract surgery with primary IOL implantation. Six months postoperatively, the enlargement of PCOA was positively correlated with follow-up duration and axial growth. Posterior capsulorhexis or capsulectomy should be performed with a diameter of 3.0 to 4.0 mm for good visual axis transparency and the protection of in-the-bag IOL.